Quality vs. quantity: the effect of relationship and number of corroborators on alibi assessments. Issue 6 (1st November 2020) - Eastwood, Joseph; Lively, Christopher J.; Snook, Brent; Snow, Mark D.
Abstract : The effect of the suspect-corroborator relationship and number of corroborators on alibi assessments was examined across two experiments. In both experiments, we explored the effect of relationship type and number of corroborators on believability, likelihood of guilt, and decision to retain the suspect as the primary suspect; we increased the social distance between the alibi provider and suspect and the size of difference between the number of corroborators in Experiment 2. Collectively, our results support Olson and Wells' taxonomy of alibi believability as (a) any form of person evidence mitigates pre-alibi judgments of guilt (although there is a ceiling effect), and (b) alibis corroborated by non-motivated others were judged more favourably than those corroborated by motivated others. Our results lend support toward extending the original taxonomy to include the number of corroborators. The implications for the alibi assessments are discussed.